Multi-Criteria Model to Assess the Potentials of Cat Ba National Park to Develop Tourism Tied to Conservation - Thu Nhung , Nguyen; Thi, Thu Hoa Le; Le, Van Huong; Pham, Hoang Hai; Thi, Thu Huong Le; Thi, Thu Van Tran; Nguyen, Duc An (Ukrainian Geographical Journal, 2024)
For a sustainable tourist destination, a multi-criteria assessment is essential. The assessment results are the basis for managers to make optimal development decisions for the destination. In particular, for the nature-based tourist sites (protected areas, national parks), the assessment of tourism potentials will establish the basis for protecting, monitoring ecosystems, and managing the tourism sustainable development calendar. The Multi-Criteria Method and additional methods were applied to assess tourism potentials as well as to propose conservation measures for Cat Ba National Park in Vietnam. Through the assessment of six criteria (location/accessibility, attractiveness, tourist capacity, environmental sustainability, travel duration, and tourism infrastructure/tourism technology), the results indicate that Cat Ba National Park (Vietnam) is an attractive tourist destination with a good tourist capacity, a convenient location for tourists to move, and a long tourism time of the year. However, Cat Ba National Park is a place where environmental sustainability is still limited; its exploitation needs to be considered along with its conservation, degradation prevention, and ecosystem monitoring.
Keywords: Cat Ba National Park; tourism; conservation; Multi-Criteria